Reactivity toward daily events: intraindividual variability and change in recurrent depression : a measurement burst study - Schricker, Isabelle; Nayman, Sibel; Reinhard, Iris; Kühner, Christine (Behaviour research and therapy, 2023)
In Major Depressive Disorder, first evidence shows heightened mood-reactivity toward daily events. Related longitudinal studies in remitted patients with recurrent major depression are lacking. Long-term changes in such short-term within-person associations can be analysed via measurement burst designs. Two bursts, separated by approximately 4.4 years, consisted of a baseline session and an Ambulatory Assessment (burst-1: 3 days, burst-2: 5 days). Via smartphone, 54 initially remitted patients with recurrent major depression indicated their negative and positive affect, rumination, self-acceptance, and the occurrence of negative and positive daily events ten times and collected saliva cortisol samples five times per day. In bursts with higher depression levels, patients showed blunted negative affect- and cortisol-reactivity and stronger decreases in positive affect and self-acceptance toward negative daily events, as well as stronger increases in self-acceptance following positive daily events. However, patients with higher depression levels demonstrated stronger ruminative stress-reactivity within bursts. Furthermore, patients with higher depression levels showed an increase of affective stress-reactivity over bursts, such that negative affect more strongly increased and positive affect more strongly decreased following negative daily events over bursts. Following positive daily events, patients with higher depression levels showed stronger decreases in negative affect within bursts and a decrease of self-acceptance-reactivity over bursts. To conclude, measurement burst designs enable to examine intraindividual variability and change of micro-level processes, and possible moderators thereof, potentially providing prognostic information for the course of recurrent major depression.